2008
DOI: 10.1179/174328108x284598
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coke breeze particle size on quality of sinter

Abstract: Iron ore sintering is an extremely complex process involving fuel combustion to generate heat and reducing gases like CO. This heat allows physicochemical, solid and solid-liquid reactions to form liquids of complex components as fuel particles are consumed and cooling processes allow the formation of solid mineral phases. At JSW coke breeze from coke ovens is used as solid fuel in sinter. The properties (size) of the solid fuel play a very important role in determining the sinter microstructural properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
1
15
0
5
Order By: Relevance
“…So far, studies have indicated a potential for emissions reduction and productivity increase using biomass in agglomeration of iron ore [3][4][5][6][7][8][9][10][11][12][13][14]. However, a more thorough analysis is necessary with respect to the impact of biomass on the properties of the final product, blast furnace agglomerate, which must meet strict quality requirements in terms of the blast furnace process.…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies have indicated a potential for emissions reduction and productivity increase using biomass in agglomeration of iron ore [3][4][5][6][7][8][9][10][11][12][13][14]. However, a more thorough analysis is necessary with respect to the impact of biomass on the properties of the final product, blast furnace agglomerate, which must meet strict quality requirements in terms of the blast furnace process.…”
Section: Introductionmentioning
confidence: 99%
“…O combustível mais utilizado nas plantas de sinterização é a moinha de coque (finos de coque) (13,1,16) .…”
Section: Combustíveisunclassified
“…Os combustíveis para sinterização devem possuir granulometria entre 1,0 e 3,0mm, poder calorífico e reatividade suficientes para fornecer energia durante o processo (1,13) .…”
Section: Combustíveisunclassified
See 2 more Smart Citations